Off-line programming industrial robots based in the information extracted from neutral files generated by the commercial CAD tools - Bottazzi, Vitor Santos (2006)
In order for a robotic manipulator to perform useful work, it must be programmed to accomplish the desired task or motion cycle. Nowadays industrial robots generally require a tremendous amount of programming to make them useful. Their controllers are very sophisticated, the commercial robot programming environments are typically closed systems and the programming languages varies from manufacturer to manufacturer. Despite the great evolution of the industrial robots controllers, in the majority of the industrial applications, the robot programming is made, using one of the following ways: • Manual on-line programming; • Off-line programming; Manual on-line programming refers to physically teaching a robot the required trajectory, through interaction with teach pendant or other similar device (Lee & ElMaraghy, 1990). This programming kind presents the following disadvantages: very slow, it needs that the robot is available, difficulty in the handling of equipments, need some practice in the language used by the robot, and technical knowledge to understand the operation of the equipment. These disadvantages are very expensive in the industry because the productive process needs to stop for a long time. One simple approach to solve some disadvantages described above is the Off-line programming environments. These environments are based in graphical simulation platforms, in which the programming and execution process are shown using models of the real objects. Consequently, the robot programmer has to learn only the simulation language and not any of the robot programming languages. Other benefits in off-line programming environments include libraries of pre-defined high-level commands for certain types of applications, such as painting or welding, and the possibility to assess the kinematics feasibility of a move, thus enabling the user to plan collision-free paths. The simulation may also be used to determine the cycle time for a sequence of movements. These environments usually provide a set of primitives commonly used by various robots, and produce a sequence of robot manipulator language primitives such as ”move” or ”open gripper” that are then downloaded in the respective robot controllers. However, the off-line programming tools based in graphically 3D representation presents several problems in many industry applications, particularly, when the robot task or the robot trajectory needs frequent changes, for example: in welding applications where the configuration of the pieces to weld change frequently (the size, the shape, etc.); the robot painting and gluing applications can have similar problems. Nowadays, the CAD tools are often used in the industry to develop and to document the products and its manufacture. There are a lot of commercial CAD tools, like, AutoCAD, SolidWorks, Ideas and Cimatron, having each tool its own file format. However, it is possible to export the information of these pieces, in a neutral file format, namely: STL, IGES, STEP and SET formats. This work presents one solution for programming different robots based in the relevant information extracted from neutral files. The solution implemented was tested in the industrial robots Mitsubishi (Mitsubishi Move Master Industrial Robot) and ABB (model IRB 140 with IRC5 controller). This chapter is organized as follows: section 2 presents an overview about the format of neutral files (STL, IGS, STEP and SET); in the section 3, the algorithms for extraction of the relevant information from the neutral files are described; in the section 4, the developed tool for code generation for different industrial robots is presented; section 5 and 6 present the results and conclusions; section 7 presents future work.